2020
DOI: 10.2147/cmar.s241959
|View full text |Cite
|
Sign up to set email alerts
|

<p>Novel Prognostic Nomograms for Predicting Early and Late Recurrence of Hepatocellular Carcinoma After Curative Hepatectomy</p>

Abstract: Aim: Hepatectomy is the main curative method for patients with hepatocellular carcinoma (HCC) in China. Unfortunately, high recurrence rate after hepatectomy poses negative impact on the prognosis of patients. This study aimed to develop prognostic nomograms to predict early recurrence (ER) and late recurrence (LR) of HCC after curative hepatectomy. Patients and Methods: Total of 318 HCC patients undergoing curative hepatectomy from January 2012 to January 2018 were retrospectively recruited. Potential risk fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 78 publications
(113 reference statements)
0
27
1
Order By: Relevance
“…Irregular tumour margin was confirmed as a reliable predictor of microvascular invasion (MVI)[ 30 ]. MVI has been regarded as an important risk factor affecting the prognosis of HCC patients after treatment[ 31 ]. In our study, irregular tumour margin had a significant effect on patient survival, indicating that it also had an increasing trend in the development of TACE refractoriness.…”
Section: Discussionmentioning
confidence: 99%
“…Irregular tumour margin was confirmed as a reliable predictor of microvascular invasion (MVI)[ 30 ]. MVI has been regarded as an important risk factor affecting the prognosis of HCC patients after treatment[ 31 ]. In our study, irregular tumour margin had a significant effect on patient survival, indicating that it also had an increasing trend in the development of TACE refractoriness.…”
Section: Discussionmentioning
confidence: 99%
“…The early/late recurrence groups are then determined according to the defined recurrence time point, and the two groups are compared to find the risk factors for early recurrence. 15 , 23 We consider that those methods have the following shortcomings. 1) The difference between the two groups may represent only the difference in the composition of the variables between patients with early/late recurrence, and although the study population is limited to the recurrence group, the results of the analysis may not necessarily indicate risk factors for recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…and BCLC staging. Many previous studies have been conducted to analyze the risk factors for the early recurrence of HCC after hepatectomy/ablation based on imaging 13 or clinical-pathological factors, 14 , 15 and corresponding predictive models have been developed. In patients with HCC undergoing hepatectomy, those in whom HCC is combined with MVI are more likely to experience early recurrence than those without MVI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference in patient inclusion criteria (patients with and without hepatitis B) and the cut-off time point (1 year) for early and late HCC recurrence might have resulted in the diverse outcomes. Recently, Xu et al (28) also investigated the risk factors of early and late recurrence of HCC. They adopted a 2-year cut-off time point to classify early and late recurrence of HCC, and found that ALBI was an independent risk factor for early recurrence whereas NLR correlated to late recurrence of HCC, which was different from our outcomes.…”
Section: A B Cmentioning
confidence: 99%